SURGICAL MANAGEMENT OF A NEONATE WITH INTERRUPTED AORTIC ARCH, TRANSPOSITION OF THE GREAT ARTERIES, AND TRICUSPID ATRESIA - Litwin, S. Bert (1975)
A critically ill infant presented to our Center with congestive heart failure due to Type A interrupted aortic arch, D-transposition of the great arteries, tricuspid atresia, a large ventricular septal defect, and a closing ductus arteriosus. Partially corrective surgery including aortic arch reconstruction, ductal division, and pulmonary artery banding was successful. Future total correction is planned.